Impact of Obesity on the Metabolic Control of Type 2 Diabetes: Results of the Turkish Nationwide Survey of Glycemic and Other Metabolic Parameters of Patients with Diabetes Mellitus (TEMD Obesity Study) - (:unkn) unknown (KARGER, 2019)
Background: Obesity is the main obstacle for metabolic control in patients with type 2 diabetes. Turkey has the highest prevalence of obesity and type 2 diabetes in Europe. The effect of obesity on the metabolic control, and the macro-and microvascular complications of patients are not apparent. Objectives: This nationwide survey aimed to investigate the prevalence of overweight and obesity among patients with type 2 diabetes and to search for the impact of obesity on the metabolic control of these patients. We also investigated the independent associates of obesity in patients with type 2 diabetes. Methods: We consecutively enrolled patients who were under follow-up for at least 1 year in 69 tertiary healthcare units in 37 cities. The demographic, anthropometric, and clinical data including medications were recorded. Patients were excluded if they were pregnant, younger than 18 years, had decompensated liver disease, psychiatric disorders interfering with cognition or compliance, had bariatric surgery, or were undergoing renal replacement therapy. Results: Only 10% of patients with type 2 diabetes (n = 4,648) had normal body mass indexes (BMI), while the others were affected by overweight (31%) or obesity (59%). Women had a significantly higher prevalence of obesity (53.4 vs. 40%) and severe obesity (16.6 vs. 3.3%). Significant associations were present between high BMI levels and lower education levels, intake of insulin, antihypertensives and statins, poor metabolic control, or the presence of microvascular complications. Age, gender, level of education, smoking, and physical inactivity were the independent associates of obesity in patients with type 2 diabetes. Conclusion: The TEMD Obesity Study shows that obesity is a major determinant of the poor metabolic control in patients with type 2 diabetes. These results underline the importance of prevention and management of obesity to improve health care in patients with type 2 diabetes. Also, the results point out the independent sociodemographic and clinical associates of obesity, which should be the prior targets to overcome, in the national fight with obesity. (c) 2019 The Author(s) Published by S. Karger AG, Basel
Keywords: Obesity; Type 2 diabetes; HbA1c; Blood pressure; Lipid metabolism; CARDIOVASCULAR RISK; BLOOD-PRESSURE; SMOKING; DISEASE; WEIGHT; ASSOCIATION; PREVALENCE; ATTAINMENT; OVERWEIGHT